2020
DOI: 10.1155/2020/8386160
|View full text |Cite
|
Sign up to set email alerts
|

Results from the Population-Based Gutenberg Health Study Revealing Four Altered Autoantibodies in Retinal Vein Occlusion Patients

Abstract: Purpose. Retinal vein occlusion (RVO) is the second most common retinal vascular disease and a major cause of visual impairment. In this study, we aimed to observe whether RVO cases have different antibody profiles as a new potential risk factor and whether a conversion of retinal vein occlusion (RVO) to neovascular glaucoma (NVG), one of the major complications, is occurring within a 5-year timeframe. Methods. We performed a nested case-control study (1 : 4) within the Gutenberg Health Study (GHS), a populati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Superoxide dismutase (SOD) has the effect of anti-thrombomodulin methionine oxidation, promoting protein C activation and protecting mouse arterial and venous thrombosis ( 91 ). SOD, nerve growth factor Neurotrophin-3 (NFT3), dermal protein, and SRP14 are serum autoantibodies related to RVO ( 92 ). Through in vitro studies, the prethrombotic effects associated with SOD were observed to increase platelet activation, tissue factor activity, and anticoagulation disorders resulting in thrombus ( 91 ).…”
Section: Risk Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Superoxide dismutase (SOD) has the effect of anti-thrombomodulin methionine oxidation, promoting protein C activation and protecting mouse arterial and venous thrombosis ( 91 ). SOD, nerve growth factor Neurotrophin-3 (NFT3), dermal protein, and SRP14 are serum autoantibodies related to RVO ( 92 ). Through in vitro studies, the prethrombotic effects associated with SOD were observed to increase platelet activation, tissue factor activity, and anticoagulation disorders resulting in thrombus ( 91 ).…”
Section: Risk Factorsmentioning
confidence: 99%
“…The role of Factor V Leiden, PC, PS, antithrombin (AT) in RVO is controversial ( 92 , 109 ). Kuhli-Hattenbach et al ( 116 ) found that AT, PC, PS, and Heparin Cofactor II levels were significantly less in control groups than in patients ≤ 45 years old.…”
Section: Risk Factorsmentioning
confidence: 99%
“…Beneath influencing the T cell responses, the composition of the B cell repertoire, and therewith the entirety of natural antibodies, is largely dependent on interactions with the commensal microflora [22,23]. Both, alterations in the GM and changes in the natural antibody repertoire are associated with different diseases [24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%